Bidirectional functions of thrombin on fibrinolysis: Evidence of thrombin-dependent enhancement of fibrinolysis provided by spontaneous plasma clot lysis. Issue 143 (July 2016) - Tomczyk, Martyna; Suzuki, Yuko; Sano, Hideto; Brzoska, Tomasz; Tanaka, Hiroki; Urano, Tetsumei
Abstract: Besides procoagulant activity, thrombin exhibits anticoagulant and profibrinolytic activities. We demonstrated that the euglobulin clot lysis time (ECLT) was shortened by endogenously generated thrombin as a result of the inactivation of plasminogen activator inhibitor type 1 (PAI-1). In contrast, thrombin suppressed fibrinolytic activity through the activation of thrombin activatable fibrinolysis inhibitor (TAFI). Here, using three different clot lysis assays of the ECLT, the tissue plasminogen activator supplemented plasma clot lysis time (tPA-PCLT) and the spontaneous plasma clot lysis time (s-PCLT), we analyzed how the coagulation process modifies fibrinolysis. The ECLT was shortened by exogenously supplemented thrombin in a dose-dependent manner in the absence of calcium ion (Ca ++ ), whereas this shortening was not observed in the presence of Ca ++ where endogenous prothrombin was effectively activated to thrombin. This shortening was also not observed for the tPA-PCLT, in which tPA is supplemented in excess and PAI-1 activity is mostly lost. On the contrary, thrombin dose-dependently prolonged the tPA-PCLT, which was mostly abolished by inhibitors of carboxypeptidase and activated FXIII, suggesting that the prolongation is TAFI- and Factor XIII-dependent. The s-PCLT was shortened when thrombin generation was boosted by supplementing tissue factor and phosphatidylserine together with Ca ++, which was more apparent in the presence of inhibitors of activated FXIII and activated TAFI. Thus, thrombin appeared to express its enhancing effect on fibrinolysis even in plasma, in addition to its inhibiting effect. These bidirectional functions of thrombin on fibrinolysis seem to take place on demand under different environments to maintain adequate vascular blood flow. Highlights: Boosted thrombin generation shortened the spontaneous plasma clot lysis time. The shortening was apparent when the inhibitors of FXIIIa and TAFIa existed. The shortening by thrombin was masked when tPA was added to overcome PAI-1.